Implementasi rencana strategis badan pemberdayaan masyarakat dan desa dalam upaya pengembangan badan usaha milik desa di kabupaten kotawaringin barat - Wahyudi, Aji (Jurnal Ilmiah Administrasi Publik, 2016)
The development of village-owned enterprises (BUMDes) currently is one of the flagship programs of the central government and became policy in an effort to build rural areas. In West Kotawaringin Regency, the implementation of the policy beyond the performance indicators that have been set in the strategic plan and the Village Community Empowerment Board (BPMD) of West Kotawaringin Regency, because BUM Desa development program has not been specifically addressed in the strategic plan BPMD. The results of this study indicate that the implementation of a policy that goes well, the need for cooperation between the two parties, the parties implementing policies that can translate a policy to operations in the field, and the target group policy, demonstrated by their attitude in accepting a policy.